2017
DOI: 10.1007/430_2017_8
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to the Zeolite Structure-Directing Phenomenon by Organic Species: General Aspects

Abstract: During the last years, a tremendous progress has been achieved in the application of new zeolite materials in many different sectors through different pioneering innovations in the field of zeolite synthesis. At the very core of the production of these new zeolite materials lies the use of organic species as structuredirecting agents (SDA), which has been recognized as the most important factor to determine the zeolite product rendered after the crystallization process. These organic species organize the inorg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 167 publications
(218 reference statements)
5
45
0
Order By: Relevance
“…Since the last two decades we have been exploring the structure-direction ability of non-quaternary imidazolium cations in fluoride media. 9 In the case of imidazolium-based dications we have found consistent evidence of length-dependent structure-direction effects. For instance, dications based on 1-methylimidazolium tend to give zeolite TON (10MR) as the default phase, and only for n = 4, 8 and 9, MFI appears under highly concentrated conditions.…”
Section: Introductionsupporting
confidence: 55%
“…Since the last two decades we have been exploring the structure-direction ability of non-quaternary imidazolium cations in fluoride media. 9 In the case of imidazolium-based dications we have found consistent evidence of length-dependent structure-direction effects. For instance, dications based on 1-methylimidazolium tend to give zeolite TON (10MR) as the default phase, and only for n = 4, 8 and 9, MFI appears under highly concentrated conditions.…”
Section: Introductionsupporting
confidence: 55%
“…Such interactions occur early during the formation of the zeolite nuclei. The success of OSDA for particular zeolite framework depends on several factors including their size, shape, hydrophobicity/hydrophilicity, hydrothermal stability, and their rigidity/flexibility …”
Section: Roles Of Organic Small Moleculesmentioning
confidence: 99%
“…In particular, we have found that the presence of such H-bond donor and acceptor groups within the molecule provides a very rich conformational space, which in turn alters the resulting supramolecular chemistry and the structure-directing behavior of these chiral SDAs [35,37,[39][40][41][42]. Moreover, we have shown that 13 C NMR spectroscopy can be very useful for monitoring the conformational space of these organic species upon confinement in nanoporous spaces [35], revealing stabilization of particular conformations under confinement that are unstable in open spaces (in solution). On the other hand, the occurrence of diastereoisomerism can also notably alter the outcome of a crystallization route [43][44][45].…”
Section: Introductionmentioning
confidence: 96%
“…Hence, in order to gain advantage of confinement effects in diverse applications it is crucial to adequately control the zeolite porous architecture that is to be used. In this context, the main control that zeolite scientists have gained over the outcome (in terms of topological framework) of a zeolite hydrothermal synthesis is through the use of the so-called organic structure-directing agents (SDAs) [9][10][11][12][13]. These are typically ammonium-based organic cations that are added to the synthesis gels, and provide a control on the crystallizing zeolite framework by host-guest size-and shape-relationships.…”
Section: Introductionmentioning
confidence: 99%